IMPROVING SPEAKING SKILL THROUGH DIALOG METHOD AT THE ELEVENTH STUDENTS SMAN 1 PAMANUKAN ACADEMIC YEAR 2021/2022 (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
Speaking is a learning activity based on speaking directly using English, while according to Ladouse (in Nunan, 1991: 23) speaking is an activity to explain someone in a certain situation or an activity to report something. Because learning speaking is very important because speaking itself is a provision for ourselves, so that in the future the benefits of speaking alone can be brave, we can speak in public, increase knowledge, and are required to be active in speaking. Moreover speaking is very much needed in the international field.The use of Speaking by using dialogue techniques will greatly assist students in increasing the courage to speak in public, increasing knowledge and being active in speaking. Because most of the students become less confident when having dialogues in front of the class and are nervous, therefore increasing dialogue techniques will increase self-confidence and will add insight when they want to talk to find new ideas and topics and this technique is one alternative way to improve speaking skill.
Keywords: Improving; Speaking; Dialog Methode